2012
DOI: 10.1007/978-1-4614-4118-2_7
|View full text |Cite
|
Sign up to set email alerts
|

The Alternative C5a Receptor Function

Abstract: When acute inflammatory states are induced by treatment with chemical mediators in C5-deficient mice, neutrophil influxes are commonly decreased. Therefore, the neutrophil C5a receptor (C5aR) is believed to be a member of the pro-inflammatory receptors. However, C5aR deficiency endows mouse neutrophils with increased sensitivity to Pseudomonas aeruginosa. We have demonstrated that C5aR accepts not only C5a but also ribosomal protein S19 (RP S19) oligomers. RP S19 oligomers released from apoptotic cells promote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Neutrophils in other organs i.e. the lung are important part of the early innate immune response, as early as 4 hr post exposure to different antigen challenges [26,27], and can be involved in long term inflammation [28]. After the initial infiltration of the neutrophils into the tissue, the resident macrophages (Kupffer cells) may take over the immune response to the nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils in other organs i.e. the lung are important part of the early innate immune response, as early as 4 hr post exposure to different antigen challenges [26,27], and can be involved in long term inflammation [28]. After the initial infiltration of the neutrophils into the tissue, the resident macrophages (Kupffer cells) may take over the immune response to the nanomaterials.…”
Section: Resultsmentioning
confidence: 99%
“…The RP S19 polymer does not induce a C5aR-mediated downstream signal but stimulates RGS3 expression via the C5aR on neutrophils (Nishiura et al, , 2009(Nishiura et al, , 2010a. Therefore, we suggested that RGS3 expression via de novo-synthesized C5aR on neutrophils participates in the shortening of the cell lifespan (Nishiura, 2013;Nishiura et al, 2013).…”
Section: Introductionmentioning
confidence: 84%
“…C5a is generally cleaved from C5 (a plasma protein released from hepatocytes) by C5 convertase at the inflammatory phase of acute inflammation [1] . The chemotactic potency of neutrophils is usually suppressed in C5-deficient acute inflammation mouse models [2] .…”
Section: Introductionmentioning
confidence: 99%